The Fornier family in the politics of Antique, 1949-1969. - Ledesma, John Ralph M.
This is a descriptive study of the Fornier as a political family in the province of Antique. The study utilized interview and archival research as the methods of gathering pertinent data. The study found out three things: first that the Forniers gained a foothold in Antique's electoral politics through political leadership legacy, especially by Tobias; second that they were able to maintain their political dominance through patronage using government resources; and third, economic, particulary infrastructural, contributions of the Forniers in Antique. The study concludes that a political family like the Forniers of Antique can enter, and maintain its dominance when the resources of the state is at their disposal.